Educational effectiveness of gynaecological teaching associates: a multi‐centre randomised controlled trial. (18th January 2016) - Duffy, JMN; Chequer, S; Braddy, A; Mylan, S; Royuela, A; Zamora, J; Ip, J; Hayden, S; Showell, M; Kinnersley, P; Chenoy, R; Westwood, OM; et al.
Abstract : Objective: To evaluate, among medical students learning the female pelvic examination, the added benefits of training by gynaecological teaching associates compared with training involving a manikin only. Design: Randomised controlled trial. Setting: Nine university teaching hospitals. Population: Ninety‐four medical students recruited prior to commencing a 4‐week obstetrics and gynaecology rotation. Methods: The control training consisted of lectures, demonstration of the pelvic examination on a manikin, and opportunities to practise on this low‐fidelity simulation ( n = 40). The experimental group received additional gynaecological teaching associate training, delivered by pairs of experienced associates to groups of four medical students ( n = 54). Main outcome measures: Outcomes measured at the end of the rotation included knowledge of the correct order of examination components (Yes/No), and student comfort [Likert scales anchored between 1 (very uncomfortable) and 4 (very comfortable) on four items] and confidence [Likert scales anchored between 1 (No) and 3 (Yes) on six items]. The primary outcome, measured at the end of the academic year, was the objective structured clinical examination of a female pelvis (score range 0–54). Results: At baseline, the groups were similar in age, gender, and ethnicity. At the end of the clinical rotation, when compared with the control intervention, the experimental intervention had a moderate effect on student knowledge [difference 29.9% (95% CI 11.2–48.6%); P = 0.002] and confidence [difference 1 (95% CI 0‐2); P < 0.001], and a large effect on student comfort [difference 1.8 (95% CI 0.6–3.0); P = 0.004]. At the end of the academic year, the experimental intervention had no impact on skills compared with the control [difference 2 (95% CI–1 to 4); P = 0.26]. Conclusions: Among medical students taught the female pelvic examination by low‐fidelity simulation, additional training by gynaecology teaching associates improved knowledge, comfort, and confidence at the end of the clinical rotation but did not improve examination skills at end of the academic year. Abstract : This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights13824